Analisis Sistem Dalam Peningkatan Kinerja Manajerial Di Sekolah Dasar - Nazla Sofi Adinda; Dea Nadhira Mulyadi; Sarah Nabila Pulungan (CV. ITTC INDONESIA, 2024)
Abstract This study aims to analyze the system in improving managerial performance in elementary schools. Effective managerial performance is the key to realizing the school's vision and mission, improving the quality of education, and creating a conducive learning environment. This study uses a qualitative approach with a case study method in several elementary schools. Data were collected through interviews, observations, and document analysis related to managerial policies and practices. The results of the study indicate that improving managerial performance is influenced by several factors, including human resource management, implementation of information technology, effective communication systems, and government policy support. A data-based managerial system is one of the important innovations that can improve the efficiency and effectiveness of decision making. In addition, training and development of principal and managerial staff competencies have been shown to contribute significantly to improving performance. This study recommends strengthening the performance evaluation system periodically and implementing a quality-based management strategy to achieve educational goals. By optimizing the existing system, elementary schools can improve institutional accountability and competitiveness. These findings are expected to contribute to the development of educational management at the elementary level.